Tools to Fight Boredom: FLOSS and GNU/Linux for Artists Working in the Field of Generative Music and Software Art. - de Valk, Marloes (Contemporary Music Review, 2009)
This article takes a look at the impact the operating system, programming languages and software, as a whole, have on the practice of artists working in the field of generative music and software art. Proprietary operating systems lack the openness needed to create an environment that fulfills the specific needs of artists and musicians who program and programmers who produce art and music. 'Hackability', the possibility to take things apart, modify, adjust, and improve, is an ever more important aspect that software artists and electronic musicians seek to include in their production environment. GNU/Linux and Free/Libre/Open Source Software (FLOSS) possess this feature, and many more, providing artists with a truly creative and open environment, free of unnecessary technical limitations, predetermined interaction, lack of control over the work environment and dependence on software companies.